PENGARUH PROFIT MARGIN, ASSETS TURNOVER DAN LEVERAGE TERHADAP SUSTAINABLE GROWTH RATE PADA PERUSAHAAN SEKTOR JASA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Nasim, Arim; Rizki Irnama, Fetti (Program Studi Akuntansi FPEB UPI, 2015)
This study aims to determine the effect of Profit Margin, Assets Turnover and Leverage on Sustainable Growth Rate. The variables used are profit margin, asset turnover and leverage as independent variable and sustainable growth rate as dependent variable. This study also aims to describe the state of profit margin projected by Net Profit Margin (NPM), asset turnover proxied by Total Assets Turnover (TATO), leverage which is proxied by Debt to Equity Ratio (DER) and Sustainable Growth Rate (SGR) Service sector. This research was conducted on service sector companies listed in Indonesia Stock Exchange 2010-2012.Data obtained from website Bursa Efek Indonesia.Teknik data analysis used is multiple linear regression and use t-statistics to test the influence of each independent variable to variable Dependent partially.Previously done classical assumption test that includes data normality test, multicolinierity test, heteroskedastisitas test and autocorrelation test.Based on data normality test, multicolinierity test, heteroscedasticity test and autocorrelation test did not found any variables that deviate from the classical assumption.From the results of research Shows that profit margin positively affect sustainable growth rate, asset turnover have positive effect to sustainable growth rate, and leverage have positive effect to sustainable growth rate.